FRONT LINE. - Kernon, Barry (Author)
The article offers news briefs for authors. It is reported that literary and talent agency PFD may disband following the resignation of several of its agents. A British Court of Appeals has ruled that 'responsible journalism' is an acceptable defence in libel proceedings. An audit of publisher Elsevier Health Sciences' royalty system has identified errors in their payment of authors.